Controllable hydrogel-thermal synthesis of Mn2O3/CNT aerogels: Shape evolution, growth mechanism and electrochemical properties. (15th November 2019) - Liu, Yang; Liu, Mingxia; Zheng, Pin; Ge, Dengteng; Yang, Lili
Abstract: Manganese oxides (MnO x ) have drawn much attention due to their low cost, low toxicity, multiple valence states, excellent electrochemical properties, and have shown great potential for lithium ion batteries, supercapacitors etc. In this work, three-dimensional Mn2 O3 /CNT aerogels with controllable morphologies including nanocubes, nanorods and nanowires, are synthesized via one-step hydrogel-thermal method. The mechanism for the hydrogel-thermal synthesis has been preliminarily presented. Our experimental results demonstrate that the precursor concentration, the cationic surfactant and confined space of hydrogel play important roles in the nanostructure growth. The electrochemical performances of the Mn2 O3 /CNT aerogels as free-standing positive material of rechargeable Li-ion batteries have also been researched. It is found that the Mn2 O3 nanowires/CNT aerogels show a better rate capability and higher specific capacity of 868 mAh·g −1 at 0.2 A/g. Our research highlights that in situ growth of nanostructured materials in hydrogels may provide another strategy for the 3D porous materials with interesting structures and high performance. Graphical abstract: Unlabelled Image Highlights: Interpenetrating Mn2 O3 /CNT aerogels were prepared from in situ hydrogel-thermal method with controllable morphologies. A novel mechanism was proposed related to the cationic surfactant and confined space of hydrogel.